Controlled generation of 3D vortices in driven atomic Josephson junctions - Vijay Pal Singh; Ludwig Mathey; Herwig Ott; Luigi Amico (Proceedings of the National Academy of Sciences, 2026)
We propose an ac-driven atomic Josephson junction as a clean and tunable source of three-dimensional (3D) solitary waves in quantum fluids. Depending on the height of the junction barrier, the emitted excitations appear as vortex rings at low velocity or vorticity-free rarefaction pulses near the sound velocity, thus spanning the complete Jones-Roberts family of solitons. The Shapiro-step phenomenon renders the emission deterministic: on the first, second, third Shapiro steps, the junction ejects one, two, and three solitary excitations per drive cycle. This enables controlled generation of single- and multiexcitation configurations, allowing detailed studies of the full crossover between vortex rings and rarefaction pulses and their interaction dynamics. By Shapiro phase locking, multiexcitations are emitted in succession and interact, revealing leapfrogging motion of two and three coaxial rings and their decay via boundary-assisted, sound-mediated processes. This ac-driven protocol establishes a compact and reproducible platform for generating, classifying, and controlling 3D solitonic excitations, paving the way for precision studies of nonlinear vortex dynamics, dissipation, and quantum turbulence in trapped superfluids.